Football as a space for marketing and relationship marketing in Zimbabwe : case of selected companies - Chingwere, Mukudzei (2020)
The study heightens on the issues of football as a space for marketing and relationship marketing in Zimbabwe. The aim of this contribution is to ascertain on the rationale of companies investing money in football sponsorship. The major objective of the contribution is thus an identification of the strengths and limitations of football as a space for commercial marketing and relationship management in modern Zimbabwe. Literature review covered football as a space for marketing and also looked at relationship marketing, it also heightened on every objective and explained it in the form of theory as postulated by others who contributed before my work. Interviews and questionnaires were used for data gathering from company representatives of NetOne, Delta Beverages and BancABC the three companies under investigation. The main finding here is that football as a space for marketing relationship marketing has a positive relationship thus concluding that the platform offered by football can utilised for marketing purposes.